2001
DOI: 10.2355/isijinternational.41.209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Liquid Fe-C Phase on the Kinetics in the Carburization of Iron by CO at 1523K.

Abstract: In order to evaluate the effect of liquid Fe-C alloy produced during the carburization on the kinetics of iron carburization, the rates of carburization of iron by CO-Ar gas mixtures have been measured gravimetrically at 1 523 K and the growing rates of the liquid Fe-C layer thickness are also measured. The measurements were made under conditions for which the gas phase mass transfer was negligible. It is found that the weight gains due to the carburization reaction are almost proportional to t 2/3 within expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
2
10
2
Order By: Relevance
“…Unfortunately, most of these results [15][16][17] were found to be under the effect of mass transfer process. In the previous work, 6) based on the established chemical reaction rate constant of CO 2 dissociation on the liquid iron, it was confirmed that the rate of the carburization reaction after the formation of the liquid Fe-C phase was controlled by the reaction of: As already mentioned, no work of the carburization of molten iron with CO-H 2 has been reported. Also the rate of CO dissociation on the liquid iron has not yet been established.…”
Section: Carburization Rates Of Iron By Co-hmentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, most of these results [15][16][17] were found to be under the effect of mass transfer process. In the previous work, 6) based on the established chemical reaction rate constant of CO 2 dissociation on the liquid iron, it was confirmed that the rate of the carburization reaction after the formation of the liquid Fe-C phase was controlled by the reaction of: As already mentioned, no work of the carburization of molten iron with CO-H 2 has been reported. Also the rate of CO dissociation on the liquid iron has not yet been established.…”
Section: Carburization Rates Of Iron By Co-hmentioning
confidence: 99%
“…Relatively high S content compared with the previous study 6) was intended to decrease the chemical reaction rate by blocking the available reaction sites. The specimen was prepared by surface grinding and metallographically polishing the upper surface.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations